Accurate patient selection and multimodal treatment offer the best therapeutic option in high-risk prostate cancer. Issue 7 (July 2013) - Rozet, François; Audenet, François; Sanchez-Salas, Rafael; Galiano, Marc; Barret, Eric; Cathelineau, Xavier
High-risk prostate cancer (HRPC) has higher recurrence potential and multimodal treatment offers better outcomes in this population. The aim of this article is to comprehensively present the multimodal therapeutic options for HRPC. Review of the literature on HRPC with a literature selection based on evidence and practical considerations. Therapeutic options for localized HRPC are radio hormone therapy and radical prostatectomy with extended lymph node dissection. Selection of patients is essential to define individualized therapeutic strategy and timing for every modality should come as a consensus of medical supported evidence. Accurate patient selection and multimodal treatment offer the best therapeutic option in HRPC.